De la carte postale au selfie : histoires de présences médiatisées - Marina Merlo (Contextes)
This article undertakes an archaeological approach of comparison between two media practices: the postcard and the selfie. It specifically focuses on travel selfies and tourist postcards, two image practices that declare "I was here!" and "I wish you were here too" by a construction, staging, and performance of presence. In our exploration of the similarities and differences between the two practices, it will be necessary to identify how subjects share themselves, how they manage to convey a presence-effect through media. We will also question the vectorization of this presence: who is present for whom? The concepts of heterotopia and hypertopia as defined by Francesco Casetti will enable us to offer an explanation for the widespread criticism of selfies as narcissistic.